Feeding behaviour of intermittently-fed broilers and the effects of crop retention time and NSPase on digesta dynamics of barley diets - M. Ahmad; L.S. Bassi; J. Apajalahti; S.K. Sjurseth; A. Smith; B. Svihus (Animal Feed Science and Technology, 2026)

First fatal HPAIV H5N1 (Clade 2.3.4.4B) infection in a domestic cat in Italy - D. D'Annunzio; M. Moreno; T. Tosi; B. Bassi; M. Muscatello; B. Bortolami; D. Drago; F. Fusaro; M. Monne; P. Palumbo; S. Savegnago; T. Terregino; et al. (Journal of Comparative Pathology, 2025)

Wettability and sp2/sp3 ratio effects on supercapacitor performance of N-doped hydrogenated amorphous carbon nanofoam - Subrata Ghosh; Giacomo Pagani; Andrea Macrelli; Alberto Calloni; Gianlorenzo Bussetti; Andrea Lucotti; Matteo Tommasini; Raffaella Suriano; Marco Agozzino; Giorgio Divitini; Yurii P. Ivanov; Veronica Piazza; et al. (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The synthetic cathinones MDPHP and MDPV: Comparison of the acute effects in mice, in silico ADMET profiles and clinical reports - Marta Bassi; Sabrine Bilel; Micaela Tirri; Giorgia Corli; Fabiana Di Rosa; Adolfo Gregori; Alaaldin M. Alkilany; Ousama Rachid; Elisa Roda; Fabrizio De Luca; Pietro Papa; Eleonora Buscaglia; et al. (NeuroToxicology, 2024)

Non-cholera Vibrio spp. invasive infections in the summer following May 2023 flood disaster in Romagna, Italy: a case series - I. Zaghi; G. Tebano; E. Vanino; G. Vandi; M. Cricca; V. Sambri; M. Fantini; F. Di Antonio; M. Terzitta; E. Russo; F. Cristini; P. Bassi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Pharmaco-toxicological effects of the novel tryptamine hallucinogen 5-MeO-MiPT on motor, sensorimotor, physiological, and cardiorespiratory parameters in mice—from a human poisoning case to the preclinical evidence - Marta Bassi; Sabrine Bilel; Micaela Tirri; Giorgia Corli; Fabiana Di Rosa; Adolfo Gregori; Alaaldin M. Alkilany; Ousama Rachid; Elisa Roda; Giorgio Zauli; Carlo Alessandro Locatelli; Matteo Marti (Psychopharmacology, 2024)
Rationale The 5-methoxy-N-methyl-N-isopropyltryptamine (5-MeO-MiPT, known online as “Moxy”) is a new psychedelic tryptamine first identified on Italian national territory in 2014. Its hallucinogen effects are broadly well-known; however, only few information is available regarding its pharmaco-toxicological effects. Objectives Following the seizure of this new psychoactive substances by the Arm of Carabinieri and the occurrence of a human intoxication case, in the current study we had the aim to characterize the in vivo acute effects of systemic administration of 5-MeO-MiPT (0.01–30 mg/kg i.p.) on sensorimotor (visual, acoustic, and overall tactile) responses, thermoregulation, and stimulated motor activity (drag and accelerod test) in CD-1 male mice. We also evaluated variation on sensory gating (PPI, prepulse inhibition; 0.01–10 mg/kg i.p.) and on cardiorespiratory parameters (MouseOx and BP-2000; 30 mg/kg i.p.). Lastly, we investigated the in silico ADMET (absorption, distribution, metabolism, excretion, toxicity) profile of 5-MeO-MiPT compared to 5-methoxy-N,N-diisopropyltryptamine (5-MeO-DIPT) and N,N-dimethyltryptamine (DMT). Results This study demonstrates that 5-MeO-MiPT dose-dependently inhibits sensorimotor and PPI responses and, at high doses, induces impairment of the stimulated motor activity and cardiorespiratory changes in mice. In silico prediction shows that the 5-MeO-MiPT toxicokinetic profile shares similarities with 5-MeO-DIPT and DMT and highlights a cytochrome risk associated with this compound. Conclusions Consumption of 5-MeO-MiPT can affect the ability to perform activities and pose a risk to human health status, as the correspondence between the effects induced in mice and the symptoms occurred in the intoxication case suggests. However, our findings suggest that 5-MeO-MiPT should not be excluded from research in the psychiatric therapy field.

A multi-reference parent nested-association mapping population to dissect the genetics of quantitative traits in durum wheat - Samir Alahmad; Yichen Kang; Eric Dinglasan; Dilani Jambuthenne; Hannah Robinson; Yongfu Tao; Jason A. Able; Jack Christopher; Kai P. Voss-Fels; Filippo M. Bassi; Lee T. Hickey (Genetic Resources and Crop Evolution, 2023)

Proposal of a reliable scoring system for the histological assessment of multiorgan injury in large animal models of ischaemia and shock - C. Palmieri; L. See Hoe; W. Dyer; S. Heinsar; S. Rozencwaig; J.P. Tung; N. Bartnikowski; M. Passmore; M. Bouquet; K. Hislop; E. Wilson; g. Li Bassi; et al. (Journal of Comparative Pathology, 2023)

From COVID-19 to Green Recovery with natural capital accounting - Michael Vardon; Paul Lucas; Steve Bass; Matthew Agarwala; Andrea M. Bassi; Diane Coyle; Anthony Dvarskas; Catherine A. Farrell; Oliver Greenfield; Steven King; Martin Lok; Carl Obst; et al. (Ambio, 2023)
The COVID-19 pandemic and related social and economic emergencies induced massive public spending and increased global debt. Economic recovery is now an opportunity to rebuild natural capital alongside financial, physical, social and human capital, for long-term societal benefit. Yet, current decision-making is dominated by economic imperatives and information systems that do not consider society’s dependence on natural capital and the ecosystem services it provides. New international standards for natural capital accounting (NCA) are now available to integrate environmental information into government decision-making. By revealing the effects of policies that influence natural capital, NCA supports identification, implementation and monitoring of Green Recovery pathways, including where environment and economy are most positively interlinked.

Effects of artificial light at night on fishes: A synthesis with future research priorities - Arshpreet Bassi; Oliver P. Love; Steven J. Cooke; Theresa R. Warriner; Christopher M. Harris; Christine L. Madliger (Fish and Fisheries, 2022)
Nearly all organisms rely on natural fluctuations of light as cues for synchronizing physiological processes and behavioural actions associated with foraging, growth, sleep and rest, reproduction, and migration. Consequently, although artificial lighting sources have provided a plethora of benefits for humans, they can lead to disruptions for wild organisms. With one quarter of the human population living within 100 km of coastlines, there is great potential for artificial light at night (ALAN) to influence the physiology, behaviour and fitness of fishes. Through a review of the literature ( n = 584 publications focused on the effects of ALAN on individual organisms or ecosystems), we illustrate that most papers have concentrated on terrestrial species (59%) compared with aquatic species (20%) or a mixed approach (21%). Fishes have been underrepresented in comparison with many other taxa such as birds, insects and mammals, representing the focus of less than 8% of taxa‐specific publications. While the number of publications per year focusing on fishes has generally been increasing since the mid‐2000s, there has been a downturn in publication rate in the last few years. To understand where research related to ALAN in fishes has been focused, we partitioned studies into categories and found that publications have mostly concerned behaviour (41.0%), abundance and community structure (24.4%), and physiology (22.8%), while the longer‐term effects on fitness (6.9%) are lacking. We synthesize the research completed in fishes and outline future priorities that will help ascertain the short‐ and long‐term consequences of this relatively novel stressor for fish health and persistence.

A framework for risk-based assessment of urban floods in coastal cities - M. Dinesh Kumar; Shubham Tandon; Nitin Bassi; Pradipta Kumar Mohanty; Saurabh Kumar; Manish Mohandas (Natural Hazards, 2022)

Institutional and farm-level challenges limiting the diffusion of new varieties from public and CGIAR centers: The case of wheat in Morocco - Yigezu A. Yigezu; Zewdie Bishaw; Abdoul Aziz Niane; Jeffrey Alwang; Tamer El-Shater; Mohamed Boughlala; Aden Aw-Hassan; Wuletaw Tadesse; Filippo M. Bassi; Ahmed Amri; Michael Baum (Food Security, 2021)
Low adoption of agricultural technologies slows efforts to increase agricultural productivity and enhance rural livelihoods in developing countries. A large body of literature has sought explanations for the problem, but the focus has been mainly on micro-level farm and community factors affecting adoption. Institutional factors such as policies and market conditions, which are also important, have been largely overlooked and, few, if any, studies combine the two levels of analysis. We use Morocco as a case study to analyze institutional and farm-level factors affecting diffusion and adoption of improved wheat varieties. Results show both sides to be important. Institutional factors such as overly stringent variety testing procedures, imbalance of power among actors in the seed sector and ill-conceived variety licensing contracts limit access to seeds of more recently released varieties. Adoption of older new varieties is found to be affected by farm and farmer characteristics, but imperfect access to new seeds, sometimes associated with the failings identified above, is also a constraint. Findings signal the need for increased private engagement in seed multiplication; revised variety testing procedures; alternative royalty mechanisms; and enhanced linkages between public research and private seed companies.

Postmortem analysis of WWI human remains from Italian glaciers in rare environmental conditions - Daniel Gaudio; L. De Luca; V. Cirielli; M. Caccianiga; C. Bassi; N. Cappellozza; A. Galassi; F. Nicolis; C. Cattaneo (Archaeological and Anthropological Sciences, 2019)

Spinal GABA-B receptor modulates neutrophil recruitment to the knee joint in zymosan-induced arthritis - Gabriel S. Bassi; David do C. Malvar; Thiago M. Cunha; Fernando Q. Cunha; Alexandre Kanashiro (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

The olfactory function is impaired in patients with idiopathic inflammatory myopathies - L. Iaccarino; N. Shoenfeld; M. Rampudda; M. Zen; M. Gatto; A. Ghirardello; N. Bassi; L. Punzi; Y. Shoenfeld; A. Doria (Immunologic Research, 2014)

Selecting with markers linked to the PPVres major QTL is not sufficient to predict resistance to Plum Pox Virus (PPV) in apricot - S. Decroocq; A. Chague; P. Lambert; G. Roch; J-M. Audergon; F. Geuna; R. Chiozzotto; D. Bassi; L. Dondini; S. Tartarini; J. Salava; B. Krška; et al. (Tree Genetics & Genomes, 2014)

Radiation hybrid QTL mapping of Tdes2 involved in the first meiotic division of wheat - F. M. Bassi; A. Kumar; Q. Zhang; E. Paux; E. Huttner; A. Kilian; R. Dizon; C. Feuillet; S. S. Xu; S. F. Kianian (Theoretical and Applied Genetics, 2013)

A radiation hybrid map of chromosome 1D reveals synteny conservation at a wheat speciation locus - Monika K. Michalak de Jimenez; Filippo M. Bassi; Farhad Ghavami; Kristin Simons; Rissa Dizon; Raed I. Seetan; Loai M. Alnemer; Anne M. Denton; Münevver Doğramacı; Hana Šimková; Jaroslav Doležel; Kiran Seth; et al. (Functional & Integrative Genomics, 2013)

Wheat Zapper: a flexible online tool for colinearity studies in grass genomes - Loai M. Alnemer; Raed I. Seetan; Filippo M. Bassi; Charith Chitraranjan; Adam Helsene; Paul Loree; Steve Bou Goshn; Yong Q. Gu; Ming-Cheng Luo; M. Javed Iqbal; Gerard R. Lazo; Anne M. Denton; et al. (Functional & Integrative Genomics, 2013)

Central leptin replacement enhances chemorespiratory responses in leptin-deficient mice independent of changes in body weight - Mirian Bassi; Humberto Giusti; Cristiane Mota Leite; Janete A. Anselmo-Franci; Jussara M. do Carmo; Alexandre A. da Silva; John E. Hall; Eduardo Colombari; Mogens L. Glass (Pflügers Archiv - European Journal of Physiology, 2012)

Origin and resedimentation of rhodoliths in the Late Paleocene flysch of the Polish Outer Carpathians - Stanisław Leszczyński; Bogusław Kołodziej; Davide Bassi; Ewa Malata; M. Adam Gasiński (Facies, 2012)

A context-inclusive approach to support energy policy formulation and evaluation - Andrea M. Bassi (Regional Environmental Change, 2011)

The maximum age of Hawaiian terrestrial lineages: geological constraints from Kōko Seamount - David A. Clague; Juan C. Braga; Davide Bassi; Paul D. Fullagar; Willem Renema; Jody M. Webster (Journal of Biogeography, 2010)
Aim To determine if Kōko Seamount submerged below sea level before Kure Island and Pearl and Hermes Reef formed, resulting in a period in which there were no extant islands. A period with no islands would eliminate prior terrestrial and shallow marine biotas that could migrate from island to island and require a restart of colonization from distant shores to populate the younger islands of the Hawaiian volcanic chain. Location Emperor Seamount Chain, north‐central Pacific Ocean. Methods We estimate subsidence rates for Kōko Seamount using ages determined from fossil large foraminifera and Sr‐isotopes, and maximum depths using palaeodepth estimates based on coralline algae. These data are combined with palaeolatitude changes as the Pacific Plate moved northwards, sea level variations, and sea surface temperature variations at the seamount through time to reconstruct the time and causes of submergence. Results Rounded carbonate clasts include three facies: zooxanthelate corals, bioclastic packstones to rudstones, and rhodolith floatstones. Two rudstones contain relatively deep‐water, coralline algal rhodoliths and large foraminifera indicative of Aquitanian (20.4–20 Ma) and Burdigalian (20–16 Ma) stages of the Early Miocene, consistent with Sr‐isotope ages of algae and one sample of large foraminifera. Corals grew on Kōko Seamount from c . 50 to 27.1 ± 0.4 Ma, the youngest Sr‐isotope age of a coral sample. These shallow, warm‐water coral reefs came under increasing stress as the volcano subsided at 0.012 ± 0.003 mm yr −1 , and migrated northwards, and as global climate cooled. The summit submerged and shallow coral reef growth ceased before 29 Ma, probably around 33 Ma. The volcano continued its slow subsidence, and deep‐water carbonates accumulated until they too were unable to keep pace, dying out at c . 16 Ma. Main conclusions The final submergence of the summit of Kōko Seamount by about 33 Ma confirms that biota on older Hawaiian–Emperor Islands could not have migrated from island to island along the entire chain to eventually colonize the present Hawaiian Islands. There was a period between at least 33 and 29 Ma in which no islands existed, and distant colonization had to repopulate the younger portion of the Hawaiian chain, which began to emerge between about 29 and 23 Ma.

Bitterness inheritance in apricot (P. armeniaca L.) seeds - P. Negri; D. Bassi; E. Magnanini; M. Rizzo; F. Bartolozzi (Tree Genetics & Genomes, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Photosynthesis research in Italy: a review - Giorgio Forti; Angela Agostiano; Roberto Barbato; Roberto Bassi; Enrico Brugnoli; Giovanni Finazzi; Flavio M. Garlaschi; Robert C. Jennings; Bruno Andrea Melandri; Massimo Trotta; Giovanni Venturoli; Giuliana Zanetti; et al. (Photosynthesis Research, 2006)

Plasticity of repetitive DNA in response to metal stress in Bryophytes - P. Bassi; A. Basile; M. Ferraro; M. Masi; D. Migliaccio; G. Morelli; E. Napolitano (Plant Biosystems, 2006)

A Zea mays 39-kDa thylakoid transglutaminase catalyses the modification by polyamines of light-harvesting complexII in a light-dependent way - M. Della Mea; A. Di Sandro; L. Dondini; S. Del Duca; F. Vantini; C. Bergamini; R. Bassi; D. Serafini-Fracassini (Planta, 2004)

Mutagenicity of Antineoplastic Drug Residues Treated in Health Care Waste Autoclave - M. D. Bassi; J. Moretton (Bulletin of Environmental Contamination and Toxicology, 2003)

Suborganellar localisation and effect of light on Helianthus tuberosus chloroplast transglutaminases and their substrates - L. Dondini; S. Del Duca; L. Dall'Agata; R. Bassi; M. Gastaldelli; M. Della Mea; A. Di Sandro; I. Claparols; D. Serafini-Fracassini (Planta, 2003)

The structure of duplications on human acrocentric chromosome short arms derived by the analysis of 15p - I. Piccini; L. Ballarati; C. Bassi; M. Rocchi; A. Marozzi; E. Ginelli; R. Meneveri (Human Genetics, 2001)

Diverse prevalence of large deletions within the OA1 gene in ocular albinism type 1 patients from Europe and North America - M. Bassi; Arthur Bergen; Pierre Bitoun; Stephen Charles; Maurizio Clementi; Richard Gosselin; Jane Hurst; Richard Lewis; Birgit Lorenz; Thomas Meitinger; Ludwine Messiaen; Rajkumar Ramesar; et al. (Human Genetics, 2001)

Influence of River Water in the Detection of Cr(VI) Mutagenicity by the Ames Test - L. C. López; M. D. Bassi; J. Moretton (Bulletin of Environmental Contamination and Toxicology, 1999)

Mapping of the murine Tbl1 gene reveals a new rearrangement between mouse and human X Chromosomes - Christine M. Disteche; Mary Beth Dinulos; Maria Teresa Bassi; Rosemary W. Elliott; Elena I. Rugarli (Mammalian Genome, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Reaction of tuber-bearing Solanum species to root knot nematode, Meloidogyne incognita - K. K. Nirula; N. M. Nayar; K. K. Bassi; G. Singh (American Journal of Potato Research, 1967)